Discussion on the Feasibility of the Integration of Wind Power and Coal Chemical Industries for Hydrogen Production - Shuxia Yang (MDPI AG, 2021)
To improve the utilization rate of the energy industry and reduce high energy consumption and pollution caused by coal chemical industries in northwestern China, a planning scheme of a wind-coal coupling energy system was developed. This scheme involved the analysis method, evaluation criteria, planning method, and optimization operation check for the integration of a comprehensive evaluation framework. A system was established to plan the total cycle revenue to maximize the net present value of the goal programming model and overcome challenges associated with the development of new forms of energy. Subsequently, the proposed scheme is demonstrated using a 500-MW wind farm. The annual capacity of a coal-to-methanol system is 50,000. Results show that the reliability of the wind farm capacity and the investment subject are the main factors affecting the feasibility of the wind-coal coupled system. Wind power hydrogen production generates O2 and H2, which are used for methanol preparation and electricity production in coal chemical systems, respectively. Considering electricity price constraints and environmental benefits, a methanol production plant can construct its own wind farm, matching its output to facilitate a more economical wind-coal coupled system. Owing to the high investment cost of wind power plants, an incentive mechanism for saving energy and reducing emissions should be provided for the wind-coal coupled system to ensure economic feasibility and promote clean energy transformation.